Perspektif ekologi terhadap sikap manusia yang membelakangi ayat-ayat penciptaan dalam al-qur’an: English - Razaq, Muhammad Akbar (Maliki Interdisciplinary Journal, 2026)
The relationship between humans and the environment is characterized by mutual dependence and interconnectedness. The environment provides essential resources for human survival, while humans hold moral and spiritual responsibilities to protect and preserve it, as emphasized in religious teachings, including the concept of humans as stewards (khalifah) on Earth. However, the advancement of modern civilization has led to the misuse of human authority through excessive exploitation of natural resources, such as deforestation, pollution, and ecosystem destruction. These actions have triggered ecological imbalance, resulting in increased natural disasters, declining biodiversity, and threats to human survival. This paper examines the interdependence between humans and the environment, the destructive impacts of irresponsible human behavior, and offers solutions to restore environmental stability through raising awareness, reforesting degraded forests, and improving waste management practices. These efforts are expected to help restore ecological balance and reinforce the role of humans as guardians of Earth’s sustainability